(untitled) (Baghdad Science Journal, 2012)
A fixed callus weight of 150 mg was induced from immature embryos of three bread wheat Triticum aestivum L. genotypes (Tamos 2, El-izz and Mutant 1) cultured on nutrient medium MS) containing Polyethylene glycol (PEG-6000) supplemented with concentrations (0.0, 3.0, 6.0, 9.0 or 12.0%) to evaluate their tolerance to water stress. Cultures were incubated in darkness at temperature of 25?1 ?C. Callus fresh and dry weights were recorded and soluble Carbohydrate and the amino acid Proline concentrations were determined. Results showed that there were significant differences in studied parameters among bread wheat genotypes of which Tamos 2 was higher in callus average fresh and dry weights which gave 353.33 and 38.46 mg/cultured tube respectively. Tamos 2 was also higher in soluble Carbohydrate and Proline concentrations which gave 189.84 and 12.30 mg/g respectively. Results also showed that there was significant reduction in callus average fresh and dry weights and soluble Carbohydrates concentration as concentrations of PEG increased in cultured medium, whereas average Proline concentration increased as PEG concentrations increased. The results also revealed significant interactions among the genotypes and PEG concentrations in all studied parameters. It can be concluded thatTamos 2 genotype showed better tolerance to drought than the other two genotypes